(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text proposes to explore different ways of relating to Time, based on a reflection on the concepts of Ancestrality, Body, and Memory, particularly when associated with Afro-Brazilian and/or Afro-Indigenous traditions. In the frictions between the different time-spaces of traditional culture, the article presents other tactics of existence and resistance through the Congadas. The text also highlights successful examples of transforming teaching-learning practices within academic spaces as a tactical bet for the future. To this end, various bibliographic references on traditional culture, decolonial studies, performance studies, and identity studies are interwoven.